Corrosion-resistant and wear-resistant integrated coating, composite coating and preparation method and application of composite coating
By distributing the composite coating of protonated modified MXene nanosheets in parallel in the cathode acrylic coating, the corrosion and wear of metal materials in the marine environment are solved, and efficient corrosion and wear resistance are achieved.
Patent Information
- Application Number
- CN202411727017.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-28
Smart Images

Figure CN119432182A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of marine anti-corrosion and wear-resistant materials, and in particular to an anti-corrosion and wear-resistant integrated coating, a composite coating, and a preparation method and application of the composite coating. Background Art
[0002] In the marine environment, factors such as salt, oxygen, microorganisms and pH changes in seawater will accelerate the corrosion process of metals, resulting in a decrease in the strength and durability of metal materials. At the same time, waves, currents and sediments in the marine environment will cause continuous mechanical wear and fatigue damage to metal materials. The above phenomena severely limit the application of metals in the marine environment. my country is currently actively developing fields such as offshore wind power and deep-sea oil and gas exploration and development. However, these equipment have been immersed in seawater and the marine atmosphere for a long time, causing serious corrosion and wear of metal materials. In addition, mechanical equipment in operation often faces friction corrosion problems. The deep-sea engineering materials currently used, such as titanium alloys, copper alloys and nickel alloys, have not yet fully met the requirements of marine engineering equipment for long-life operation in rotating systems or other components. Therefore, solving the problem of component failure caused by corrosion and wear in the marine environment is an important technical challenge facing the marine engineering field.
[0003] In order to improve the corrosion and wear resistance of marine engineering equipment, innovative research is needed in material selection, surface treatment and coating technology. Water-based acrylic acid has become a substitute for traditional organic coatings due to its low volatile organic compound (VOC) content, environmental friendliness, high hardness and good adhesion. However, water-based acrylic acid has limitations in anti-corrosion and lubrication properties. In order to enhance the corrosion and wear resistance of the coating, MXene is added as a functional filler, but the hydrophilicity of MXene makes it easy to agglomerate in water. At the same time, the random distribution of MXene in the coating cannot meet the higher protection requirements of the coating, and the random distribution of MXene in the coating is also prone to poor coating uniformity, reduced mechanical strength, reduced barrier properties and other performance defects. Summary of the invention
[0004] The present application provides an anti-corrosion and wear-resistant integrated coating, a composite coating, and a composite coating preparation method and application to solve the above-mentioned problems mentioned in the background technology.
[0005] On the one hand, the present application provides an integrated anti-corrosion and wear-resistant composite coating, which includes a composite coating in which protonated modified MXene nanosheets are distributed in parallel in a cathode acrylic coating.
[0006] On the other hand, the present application provides a method for preparing an anti-corrosion and wear-resistant integrated composite coating, characterized in that the method is used to prepare the above-mentioned anti-corrosion and wear-resistant integrated composite coating, and the preparation method comprises the following steps:
[0007] 10-20 parts by weight of cathode aqueous acrylic emulsion, 0.1-0.5 parts by weight of protonated modified MXene nanosheets, 0.02-0.04 parts by weight of dispersant, 0.02-0.04 parts by weight of defoamer and 60-90 parts by weight of solvent are stirred and mixed to obtain a mixed slurry;
[0008] The mixed slurry is coated on the surface of the substrate by electrophoretic deposition technology and cured to obtain an anti-corrosion and wear-resistant integrated composite coating.
[0009] Optionally, the conditions during the electrophoretic deposition coating process are: the DC voltage is controlled at 90-120V, the curing temperature is controlled at 120-160°C, and the curing time is 30-60min.
[0010] Optionally, the method for preparing protonated MXene nanosheets comprises the following steps:
[0011] Amino modified MXene: MXene nanosheets, 2,5-diaminobenzenesulfonic acid and water are first mixed and reacted to obtain amino modified MXene nanosheets; the mass ratio of MXene nanosheets, 2,5-diaminobenzenesulfonic acid and water is (1-2): (1-2): 1;
[0012] Composite material grafted with MXene: the amino-modified MXene nanosheets, water and tetrabutyl phosphohydroxide benzotriazole lignin composite material are secondly mixed and grafted to obtain MXene nanosheets grafted with tetrabutyl phosphohydroxide benzotriazole lignin composite material;
[0013] Protonated MXene: The MXene nanosheets grafted with tetrabutylphosphobenzotriazole lignin composite material are thirdly mixed with 1 mol / L HCl solution and protonated to obtain protonated modified MXene nanosheets.
[0014] Optionally, before the amination modification of MXene, the MXene is also pretreated;
[0015] The preprocessing process includes:
[0016] After MXene and dimethyl sulfoxide are mixed, a first centrifugation is performed, and the nanosheets obtained by the first centrifugation are mixed with water, and ultrasonication and a second centrifugation are performed in sequence to obtain pretreated MXene nanosheets.
[0017] Optionally, the mass ratio of amino-modified MXene nanosheets, water and tetrabutyl phosphobenzotriazole lignin composite material is (1-2): (1-2): (2-3).
[0018] Optionally, the mass ratio of the MXene nanosheets grafted with tetrabutylphosphobenzotriazole lignin composite material and 1 mol / L HCl solution is (1-2): (100-300).
[0019] On the other hand, the present application provides an anti-corrosion and wear-resistant integrated coating, which is used to prepare the above-mentioned anti-corrosion and wear-resistant integrated composite coating, or is applied to the preparation method of the above-mentioned anti-corrosion and wear-resistant integrated composite coating. The coating includes the following preparation raw materials in parts by weight:
[0020] 10-20 parts by weight of cathode aqueous acrylic emulsion, 0.1-0.5 parts by weight of protonated modified MXene nanosheets, 60-90 parts by weight of solvent, 0.02-0.04 parts by weight of dispersant, and 0.02-0.04 parts by weight of defoamer;
[0021] The protonated modified MXene nanosheets are MXene nanosheets grafted with tetrabutyl phosphohydroxide benzotriazole lignin composite materials and protonated with 1 mol / L HCl.
[0022] Optionally, the dispersant includes one or more of BYK-104s, BYK-166 and K270;
[0023] The defoaming agent includes one or more of BYK-035, BYK-052N and BYK-077; and the solvent is water.
[0024] The present application also provides an application of an anti-corrosion and wear-resistant integrated composite coating, which is the above-mentioned anti-corrosion and wear-resistant integrated composite coating, or the anti-corrosion and wear-resistant integrated composite coating obtained by the above-mentioned preparation method, and the anti-corrosion and wear-resistant integrated composite coating is applied in the field of marine corrosion protection.
[0025] The anti-corrosion and wear-resistant integrated coating, composite coating, and composite coating preparation method and application provided in the present application realize the preparation and application of the anti-corrosion and wear-resistant integrated composite coating, and have the following beneficial effects compared with the prior art:
[0026] (1) In the composite coating provided by the present application, the cathode acrylic coating is used as the substrate, the surface of the protonated modified MXene nanosheet is positively charged, and the cathode acrylic coating is negatively charged. The protonated modified MXene nanosheet is distributed in parallel in the cathode acrylic coating, and the protonated modified MXene nanosheet forms a continuous interface and a zigzag diffusion path in the cathode acrylic coating, so that a dense barrier layer is formed between the substrate surface and the corrosive medium, so that the path for the corrosive medium to penetrate into the metal substrate and diffuse is greatly extended compared to the "maze effect". At the same time, the protonated modified MXene nanosheet is distributed in parallel in the cathode acrylic coating, making the surface of the composite coating smoother and flatter, and the uniform distribution of the protonated modified MXene nanosheet in the coating improves the uniformity of the composite coating. In this way, a continuous, stable and smooth friction protection film can be formed on the substrate surface, so that the protonated modified MXene nanosheet as a wear-resistant and anti-corrosion filler not only has excellent lubrication properties, but also has excellent corrosion resistance.
[0027] (2) A mixed slurry is obtained by stirring and mixing the cathode aqueous acrylic emulsion, protonated modified MXene nanosheets, dispersant, defoamer and solvent in parts by weight, and the mixed slurry is coated on the surface of the substrate by electrophoretic deposition technology. Under the influence of the electric field, the protonated modified MXene nanosheets are moved to the cathode and distributed in parallel in the cathode acrylic coating, which overcomes the disadvantage that the MXene nanosheets are easy to agglomerate in the coating and forms a composite coating with integrated anti-corrosion and wear-resistant properties. The present application uses electrophoretic deposition technology to prepare a composite coating, and the process is not only simple but also efficient.
[0028] (3)f + -BTA-P in MXene-P nanosheets 4444 -Lig composite materials form an adsorption film on the surface of the metal substrate to prevent the direct contact between the corrosive medium and the metal substrate, and BTA-P 4444 -Lig contains phenolic hydroxyl groups, which can effectively capture oxygen free radicals to form resonance-stabilized semiquinone free radicals, block chain reactions, and inhibit metal corrosion. + -MXene-P orientation and crack propagation direction have a certain inclination angle, which hinders the expansion of coating cracks during friction, reduces coating peeling during friction, and improves the wear resistance of cathode water-based acrylic composite coating. At the same time, the polar elements N and P in the tetrabutylphosphonium hydroxide benzotriazole lignin composite material will react with the metal substrate to form a tribochemical film during friction, enhancing the tribological properties of the coating.
[0029] (4) The high-performance anti-corrosion and wear-resistant integrated coating of the present application uses cathodic water-based acrylic emulsion as the base material, which is environmentally friendly, low in volatility, highly chemically stable and has good adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 f provided in an embodiment of the present application + - MX-P composite coating preparation process diagram;
[0032] Figure 2 f provided in an embodiment of the present application + -Surface morphology and elemental composition analysis of MXene-P nanosheets, Figure 2 Where (a) is f + -TEM image of MXene-P nanosheets, Figure 2 (b) is f + -SEM image of MXene-P nanosheets, Figure 2 Where (c) is f + - Ti element distribution map of MXene-P nanosheets measured by EDS, Figure 2 (d) is f + -N element distribution map of MXene-P nanosheets measured by EDS, Figure 2 (e) is f + -P element distribution map of MXene-P nanosheets measured by EDS;
[0033] Figure 3 MX, f-MX, f provided in an embodiment of the present application + -MX, f-MX-P, f + -Potential analysis of the MX-P surface;
[0034] Figure 4 This is a test diagram of the wear resistance of the composite coating provided in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 3 of the present application. Figure 4 (a) is the friction coefficient analysis diagram of the composite coating. Figure 4 (b) is the wear volume analysis diagram of the composite coating;
[0035] Figure 5 The SEM morphology of the wear track of the composite coating provided in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 3 of the present application is as follows: Figure 5 (a) is the SEM morphology of the wear track of comparative example 1 (WAA), Figure 5(b) is the SEM morphology of the wear track of comparative example 2 (MX / WAA), Figure 5 (c) is comparative example 3 (f + -MX / WAA) wear track SEM morphology, Figure 5 (d) is Example 3 (f + -MX-P / WAA) wear track SEM morphology. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.
[0037] On the one hand, the present application provides an integrated anti-corrosion and wear-resistant composite coating, which includes a composite coating in which protonated modified MXene nanosheets are distributed in parallel in a cathode acrylic coating.
[0038] Specifically, MXene nanosheets are two-dimensional sheet structures. The good corrosion resistance and self-lubricating properties of MXene nanosheets make them fillers in coatings. The distribution orientation of MXene nanosheets as coating fillers in the coating can be divided into three types: vertical distribution, random distribution, and parallel distribution. The barrier effect of MXene nanosheets distributed perpendicular to the horizontal direction of the coating on the corrosive medium is 0%, and the random distribution of MXene nanosheets in the coating causes the barrier effect of MXene nanosheets on the corrosive medium to be 0-100%. The random distribution of MXene nanosheets in the coating is prone to irregular arrangement of nanosheets, easy agglomeration in the coating, or more pores in the coating, which not only has an adverse effect on the anti-corrosion performance of the coating, but also easily leads to uneven shear stress distribution during friction, causing the coating to peel off and reduce the wear resistance of the coating. When MXene nanosheets are distributed parallel to the horizontal direction of the coating, the barrier effect on the corrosive medium can reach 100%.
[0039] In the composite coating provided by the present application, the cathode acrylic coating is used as the substrate, the surface of the protonated modified MXene nanosheet is positively charged, and the cathode acrylic coating is negatively charged. The protonated modified MXene nanosheet is oriented and parallel distributed in the cathode acrylic coating, and the protonated modified MXene nanosheet forms a continuous interface and a zigzag diffusion path in the cathode acrylic coating to form a composite coating, so that a dense barrier layer is formed between the substrate surface and the corrosive medium, so that the path for the corrosive medium to penetrate into the metal substrate and diffuse is greatly extended compared to the "maze effect". At the same time, the protonated modified MXene nanosheet is distributed in parallel in the cathode acrylic coating, so that the surface of the composite coating is smoother and flatter, and the mechanical strength is enhanced, and the uniform distribution of the protonated modified MXene nanosheet in the coating improves the uniformity of the composite coating, so that a continuous, stable and smooth friction protection film can be formed on the substrate surface, which is conducive to improving the wear resistance of the composite coating. Therefore, the composite coating provided by the present application has excellent anti-corrosion and wear-resistant integrated performance.
[0040] On the other hand, Figure 1 As shown, the present application provides a method for preparing an anti-corrosion and wear-resistant integrated composite coating, which is used to prepare the above-mentioned anti-corrosion and wear-resistant integrated composite coating, and the preparation method comprises the following steps:
[0041] 10-20 parts by weight of cathode aqueous acrylic emulsion, 0.1-0.5 parts by weight of protonated modified MXene nanosheets, 0.02-0.04 parts by weight of dispersant, 0.02-0.04 parts by weight of defoamer and 60-90 parts by weight of solvent are stirred and mixed to obtain a mixed slurry;
[0042] The mixed slurry is coated on the surface of the substrate by electrophoretic deposition technology and cured to obtain an anti-corrosion and wear-resistant integrated composite coating.
[0043] Specifically, a cathode aqueous acrylic emulsion, a protonated modified MXene nanosheet, a dispersant, a defoaming agent and a solvent are stirred and mixed to obtain a mixed slurry, and the mixed slurry is coated on the surface of the substrate by electrophoretic deposition technology, and solidified to obtain an integrated anti-corrosion and wear-resistant composite coating. The surface of the protonated modified MXene nanosheet is positively charged, and the cathode acrylic coating is negatively charged. Under the influence of the electric field, the protonated modified MXene nanosheet is oriented and parallel distributed in the cathode acrylic coating, overcoming the disadvantage that the MXene nanosheet is easy to agglomerate in the coating, and forming a composite coating with integrated anti-corrosion and wear-resistant properties. At the same time, the protonated modified MXene nanosheet forms a continuous interface and a zigzag diffusion path in the cathode acrylic coating, so that the diffusion path of the corrosive medium penetrating into the metal substrate is greatly extended compared to the "maze effect".
[0044] The cathode aqueous acrylic emulsion is the coating substrate, and the role of the dispersant is to prevent the center of gravity of the protonated modified MXene nanosheets from settling, maintain the suspension state of the nanosheets, and thus ensure the uniformity of the coating. The role of the defoamer is to avoid the formation of bubbles in the aqueous cathode aqueous acrylic emulsion or to remove the bubbles that have already formed in the aqueous cathode aqueous acrylic emulsion.
[0045] The cathode water-based acrylic emulsion is a copolymer of acrylate and methacrylate monomers, and the solid content of the cathode water-based acrylic emulsion is 8%-12%. The electrophoretic deposition technology has the advantages of being environmentally friendly and easy to operate, and can achieve the parallel distribution of protonated modified MXene nanosheets in the water-based cathode acrylic coating, meeting the higher protection requirements of the coating.
[0046] During the preparation of the mixed slurry, the stirring speed is 300-500 rpm, preferably 320-480 rpm, more preferably 340-460 rpm; the stirring time is preferably 50-80 min, more preferably 55-75 min, most preferably 60-70 min.
[0047] The present application realizes the preparation of an integrated anti-corrosion and wear-resistant composite coating through the above scheme. The cathode aqueous acrylic emulsion, protonated modified MXene nanosheets, dispersant, defoaming agent and solvent are stirred and mixed by weight to obtain a mixed slurry, and the mixed slurry is coated on the surface of the substrate through electrophoretic deposition technology. Under the influence of the electric field, the protonated modified MXene nanosheets are oriented and distributed in parallel in the cathode acrylic coating, thereby overcoming the disadvantage that the MXene nanosheets are easy to agglomerate in the coating, and forming a composite coating with integrated anti-corrosion and wear-resistant properties.
[0048] Optionally, the conditions during the electrophoretic deposition coating process are: the DC voltage is controlled at 90-120V, the curing temperature is controlled at 120-160°C, and the curing time is 30-60min.
[0049] Specifically, by controlling the voltage and temperature during the electrophoretic deposition process, the protonated modified MXene nanosheets are ensured to be distributed in parallel in the cathode acrylic coating, thereby forming a continuous, stable and smooth composite coating, which is beneficial to improving the corrosion and wear resistance of the substrate surface.
[0050] Among them, the DC voltage of the electrophoretic deposition technology is preferably 90V-120V, more preferably 95-110V, and most preferably 100-105V. The curing temperature is preferably 120-160°C, more preferably 130-150°C, and most preferably 135-145°C. The curing time is preferably 30-60min, more preferably 35-45min, and most preferably 38-43min.
[0051] In the present application, the thickness of the high-performance anti-corrosion and wear-resistant integrated coating obtained by electrophoretic deposition is preferably 40-60 μm, more preferably 45-58 μm, and most preferably 50-55 μm.
[0052] like Figure 1 As shown, optionally, the method for preparing protonated MXene nanosheets comprises the following steps:
[0053] Amino modified MXene: MXene nanosheets, 2,5-diaminobenzenesulfonic acid and water are first mixed and reacted to obtain amino modified MXene nanosheets; the mass ratio of MXene nanosheets, 2,5-diaminobenzenesulfonic acid and water is (1-2): (1-2): 1;
[0054] Composite material grafted with MXene: the amino-modified MXene nanosheets, water and tetrabutyl phosphohydroxide benzotriazole lignin composite material are secondly mixed and grafted to obtain MXene nanosheets grafted with tetrabutyl phosphohydroxide benzotriazole lignin composite material;
[0055] Protonated MXene: The MXene nanosheets grafted with tetrabutylphosphobenzotriazole lignin composite material are thirdly mixed with 1 mol / L HCl solution and protonated to obtain protonated modified MXene nanosheets.
[0056] Specifically, the surface of MXene nanosheets has active functional groups. The amino groups on 2,5-diaminobenzenesulfonic acid form covalent bonds and intermolecular hydrogen bonds with the surface active groups of MXene nanosheets. 2,5-diaminobenzenesulfonic acid is used to amino-modify the MXene nanosheets to enhance the hydrophilicity of the MXene nanosheets, thereby enhancing the dispersibility of MXene in the water-based acrylic coating and improving the uniformity of the composite coating.
[0057] In the step of aminated modified MXene, 2,5-diaminobenzenesulfonic acid is preferably chemically pure. The first mixing is carried out under stirring, and the stirring speed is preferably 200-300rpm, more preferably 220-280rpm, and most preferably 240-260rpm. The stirring time is preferably 0.5-3h, more preferably 2-3h, and most preferably 2h; the stirring temperature is preferably 75-85°C, more preferably 80-85°C, and most preferably 80°C; the stirring temperature is preferably achieved by oil bath heating. The mass ratio of MXene nanosheets, 2,5-diaminobenzenesulfonic acid and water is preferably (1-2): (1-2): 1, more preferably 2: (1-2): 1, and most preferably 2: 1: 1.
[0058] After the amino modification is completed, it is also preferably included in vacuum filtration and drying in sequence. The present application does not have any special limitation on the process of vacuum filtration, and conventional vacuum filtration can be performed using a filter membrane well known to those skilled in the art. In the present application, the drying method is preferably drying, the drying temperature is preferably 60° C., and the drying time is preferably 12 hours.
[0059] Since tetrabutyl benzotriazole phosphohydroxide lignin composite material (BTA-P 4444 -Lig) contains a large number of benzene rings and hydroxyl groups, which have strong interfacial adsorption properties, making BTA-P 4444 -Lig was successfully loaded onto f-MX nanomaterials through intermolecular hydrogen bonds. 4444 -Lig contains phenolic hydroxyl groups, which can effectively capture oxygen free radicals, form resonance-stabilized semiquinone free radicals, block chain reactions, and inhibit metal corrosion. At the same time, the polar elements N and P in the tetrabutylphosphonium hydroxide benzotriazole lignin composite material will react with the metal substrate to form a tribochemical film during the friction process, blocking the direct contact between the corrosive medium and the substrate surface, and enhancing the tribological properties of the composite coating. And because the tetrabutylphosphonium hydroxide benzotriazole lignin composite material is green, environmentally friendly, and has excellent anti-corrosion and lubrication properties, it can further improve the wear resistance of the composite coating.
[0060] More preferably, in the composite grafted MXene, after the amino-modified MXene nanosheets and water are ultrasonically mixed, the tetrabutyl phosphohydroxide benzotriazole lignin composite material is added for the second mixing. The frequency of ultrasonic mixing is preferably 40-80KHz, more preferably 60-80KHz, and most preferably 60KHz; the time of ultrasonic mixing is preferably 0.5-1.5h, more preferably 1-1.2h, and most preferably 1h. The present application does not have any special restrictions on the addition process of the tetrabutyl phosphohydroxide benzotriazole lignin composite material, and the process well known to those skilled in the art can be used. The second mixing is carried out under stirring, and the stirring temperature is preferably 80-90°C, more preferably 85-90°C, and most preferably 85°C; the stirring time is preferably 18-24h, more preferably 20-24h, and most preferably 20h; the stirring speed is preferably 200-300rpm, more preferably 250-300rpm, and most preferably 250rpm; the stirring temperature is preferably achieved by oil bath heating.
[0061] After the grafting is completed, it is also preferably included in sequence of vacuum filtration, washing and drying; the present application does not have any special restrictions on the process of vacuum filtration, and conventional vacuum filtration can be performed using a filter membrane familiar to those skilled in the art. In the present application, washing is preferably performed with deionized water, and the present invention does not have any special restrictions on the number of washings, and the number of washings familiar to those skilled in the art can be used. In the present invention, the drying method is preferably drying, and the drying temperature is preferably 60°C, and the time is preferably 12 hours.
[0062] In the present application, the preparation method of tetrabutylphosphonium hydroxide benzotriazole lignin composite material comprises the following steps:
[0063] 0.4 mol of benzotriazole and 0.4 mol of tetrabutylphosphonium hydroxide were added to a 500 mL single-mouth bottle, and the mixture was reacted for 24 hours under nitrogen protection. After the reaction, water was evaporated under reduced pressure, dissolved with dichloromethane, and dried over anhydrous magnesium sulfate overnight. The mixture was filtered and the solvent was evaporated under reduced pressure to obtain a light yellow transparent oily liquid, which was the ionic liquid tetrabutylphosphonium hydroxide benzotriazole (named BTA-P 4444 ), the yield is 95%. Weigh 5 grams of lignin and add it to 95g BTA-P 4444 The mixture was heated to 150 °C and stirred for 10 min to obtain a tetrabutylphosphonium hydroxide benzotriazole lignin composite material (named BTA-P 4444 -Lig).
[0064] At the same time, the MXene nanosheets grafted with tetrabutyl phosphohydroxide benzotriazole lignin composite material are protonated by 1mol / LHCl solution to obtain protonated modified MXene nanosheets, and the protonated modified MXene nanosheets are distributed in parallel in the cathode acrylic coating by electrophoretic deposition technology, which overcomes the disadvantage that the MXene nanosheets are easy to agglomerate in the coating. At the same time, the parallel arranged protonated modified MXene nanosheets form a continuous interface and a zigzag diffusion path in the cathode acrylic coating, so that the path for the corrosive medium to penetrate into the metal substrate and diffuse is greatly extended, so that the coating has excellent anti-corrosion performance. And during the friction process, due to the orientation of the protonated modified MXene nanosheets and the crack propagation direction, the expansion of the coating cracks during the friction process can be hindered, the peeling of the coating during the friction process is reduced, and the wear resistance of the cathode water-based acrylic composite coating is improved. The third mixing is carried out under stirring conditions, the stirring temperature is room temperature, and the stirring time is preferably 10-15 hours, more preferably 11-13 hours, and most preferably 12 hours. The stirring speed is preferably 200-300 rpm, more preferably 250-300 rpm, most preferably 250 rpm.
[0065] After protonation is completed, it is also preferably included in sequence of vacuum filtration, washing and drying; the present application does not have any special restrictions on the process of vacuum filtration, and conventional vacuum filtration can be performed using a filter membrane familiar to those skilled in the art. In the present application, washing is preferably performed with deionized water, and the present invention does not have any special restrictions on the number of washings, and can be performed using a number familiar to those skilled in the art. In the present invention, the drying method is preferably drying, and the drying temperature is preferably 60°C, and the time is preferably 12 hours.
[0066] Optionally, before the amination modification of MXene, the MXene is also pretreated;
[0067] The preprocessing process includes:
[0068] After MXene and dimethyl sulfoxide are mixed, a first centrifugation is performed, and the nanosheets obtained by the first centrifugation are mixed with water, and ultrasonication and a second centrifugation are performed in sequence to obtain pretreated MXene nanosheets.
[0069] Specifically, by stirring and mixing MXene and dimethyl sulfoxide, dimethyl sulfoxide increases the interlayer spacing of MXene, and then ultrasonic dispersion is used to further delaminate the MXene to obtain pretreated MXene nanosheets, which are then used for subsequent amination modification. Increasing the interlayer spacing of MXene by dimethyl sulfoxide is beneficial to the subsequent amination modification and BTA-P 4444 -Lig grafting process proceeds smoothly, improves the efficiency of amination reaction, and helps BTA-P 4444 -Grafting of Lig.
[0070] The dosage ratio of MXene to dimethyl sulfoxide is preferably 1g:50-150mL, more preferably 1g:100-150mL, and most preferably 1g:150mL. The mixing of MXene and dimethyl sulfoxide is preferably carried out under stirring, and the stirring temperature is preferably 50-65°C, more preferably 60-65°C, and most preferably 60°C; the stirring time is preferably 18-30h, more preferably 24-30h, and most preferably 24h; the stirring speed is preferably 200-300rpm, more preferably 250-300rpm, and most preferably 250rpmn; the stirring temperature is preferably achieved by oil bath heating.
[0071] The speed of the first centrifugation is preferably 3000-3600rpm, more preferably 3100-3500rpm, and most preferably 3200-3300rpm; the time of the first centrifugation is preferably 3-5min, more preferably 3.5-4.5min, and most preferably 3.8-4.2min. The nanosheets obtained by the first centrifugation are mixed with water, and ultrasonic and second centrifugation are performed in sequence. The residual dimethyl sulfoxide is removed by water washing to remove impurities from the MXene nanosheets. The MXene nanosheets are preferably Ti3C2 MXene; the particle size of the MXene nanosheets is preferably 300 mesh, and the purity is preferably greater than 99%.
[0072] In the present application, water is preferably deionized water or ultrapure water, and the ratio of the product obtained after the first centrifugation to water is preferably 1 g: 500-1000 mL, more preferably 1 g: 800-1000 mL, and most preferably 1 g: 1000 mL. In the present application, the frequency of ultrasound is preferably 40-80 KHz, more preferably 60-80 KHz, and most preferably 60 KHz, and the time of ultrasound is preferably 18-30 h, more preferably 24-30 h, and most preferably 24 h.
[0073] In the present application, the rotation speed of the second centrifugation is preferably 8500-9500 rpm, more preferably 8800-9200 rpm, and most preferably 8900-9100 rpm; the time of the second centrifugation is preferably 8-15 min, more preferably 10-15 min, and most preferably 10 min.
[0074] After the second centrifugation is completed, drying is preferably included. The drying temperature is preferably 50-65°C, more preferably 60-65°C, and most preferably 60°C; the drying time is preferably 10-15h, more preferably 12-15h, and most preferably 12h.
[0075] Optionally, the mass ratio of the amino-modified MXene nanosheets, water and tetrabutylphosphohydroxide benzotriazole lignin composite material is (1-2): (1-2): (2-3), more preferably 1:1: (2-3), and most preferably 1:1:2.
[0076] Optionally, the mass ratio of the MXene nanosheet grafted with tetrabutylphosphohydroxide benzotriazole lignin composite material and 1 mol / L HCl solution is (1-2): (100-300), more preferably 1: (100-250), and most preferably 1:200.
[0077] On the other hand, the present application provides an anti-corrosion and wear-resistant integrated coating, which is used to prepare the above-mentioned anti-corrosion and wear-resistant integrated composite coating, or is applied to the preparation method of the above-mentioned anti-corrosion and wear-resistant integrated composite coating. The coating includes the following preparation raw materials in parts by weight:
[0078] 10-20 parts by weight of cathode aqueous acrylic emulsion, 0.1-0.5 parts by weight of protonated modified MXene nanosheets, 60-90 parts by weight of solvent, 0.02-0.04 parts by weight of dispersant, and 0.02-0.04 parts by weight of defoamer;
[0079] The protonated modified MXene nanosheets are MXene nanosheets grafted with tetrabutyl phosphobenzotriazole lignin composite materials and protonated with 1 mol / L HCl.
[0080] Specifically, the cathode aqueous acrylic emulsion is preferably 12-18 parts by weight, more preferably 13-16 parts by weight. The protonated modified MXene nanosheets are preferably 0.2-0.4 parts by weight, more preferably 0.25-0.35 parts by weight. The dispersant is preferably 0.022-0.038 parts, more preferably 0.025-0.035 parts. The solvent is preferably 65-85 parts, more preferably 70-80 parts. In the present application, the solvent is preferably water, more preferably deionized water.
[0081] Optionally, the dispersant includes one or more of BYK-104s, BYK-166 and K270;
[0082] The defoamer includes one or more of BYK-035, BYK-052N and BYK-077; the solvent is water. When the dispersant / defoamer is two or more of the above specific options, the present application does not have any special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio.
[0083] The present application also provides an application of an anti-corrosion and wear-resistant integrated composite coating, which is the above-mentioned anti-corrosion and wear-resistant integrated composite coating, or the anti-corrosion and wear-resistant integrated composite coating obtained by the above-mentioned preparation method, and the anti-corrosion and wear-resistant integrated composite coating is applied to the field of marine anti-corrosion. The composite coating is preferably applied to the metal of submarine propeller sleeves or offshore oil platform transmission parts. The present application does not have any special restrictions on the application method, and the method familiar to those skilled in the art can be used.
[0084] The technical solution of the present application is described in detail below with reference to specific embodiments.
[0085] Preparation of protonated modified MXene nanosheets:
[0086] 1 g Ti3C2 MXene (particle size of 300 mesh) and 150 mL dimethyl sulfoxide (DMSO) were added to a round-bottom flask and mixed. The mixture was stirred at a constant temperature in an oil bath at 60°C for 24 hours. The obtained mixture was separated by a centrifuge (speed of 3200 rpm, time of 4 min), washed twice with water, and 0.5 g of the nanosheets obtained by centrifugation were added to 500 mL of deionized water. After ultrasonic dispersion for 24 hours (ultrasonic frequency of 60 KHz), it was centrifuged (speed of 9000 rpm, time of 10 min), and dried in an oven at 60°C for 12 hours to obtain the pretreated MXene.
[0087] 0.2 g of 2,5-diaminobenzenesulfonic acid was dissolved in 200 mL of ultrapure water to prepare a mixed solution, and 0.4 g of MXene nanosheets was added thereto. The mixture was stirred vigorously for 0.5 hours at room temperature (speed of 250 rpm) to completely disperse it. After that, it was stirred vigorously at 80°C for 2 hours, and then vacuum filtered with a filter membrane, and dried in an oven at 60°C for 12 hours to obtain amino-modified MXene nanosheets (named: f-MXene).
[0088] 0.2 g of amino-modified MXene nanosheets were dissolved in 200 mL of deionized water and ultrasonicated for 1 hour (ultrasonic frequency was 60 KHz) to obtain a uniform dispersion, and then 0.4 g of tetrabutylphosphinothiocyanate benzotriazole lignin composite material (BTA-P 4444 -Lig), heated to 90 ° C, stirred continuously for 20 h (speed of 250 rmp), vacuum filtered with a filter membrane, washed with deionized water several times, and dried in an oven at 60 ° C for 12 h to obtain a composite material grafted MXene nanosheet (named: f-MXene-P).
[0089] 0.2 g of MXene nanosheets grafted with tetrabutylphosphohydroxide benzotriazole lignin composite material was added to 200 mL of 1 mol / L HCl solution and stirred at room temperature at a speed of 250 rpm for 12 h. After vacuum filtration with a filter membrane, it was washed with deionized water several times and dried in an oven at 60 ° C for 12 hours to obtain protonated modified MXene nanosheets (named: f + -MXene-P).
[0090] Example 1
[0091] An anti-corrosion and wear-resistant integrated composite coating and a preparation method and application thereof, comprising the following steps:
[0092] (1) Composite coating preparation raw materials: by weight: 10-20 parts by weight of cathode aqueous acrylic emulsion (specifically, aqueous acrylic acid copolymerized with acrylate and methacrylate monomers, purchased from Jiangxi Gaojie Technology Co., Ltd.), 0.1 parts by weight of protonated modified MXene nanosheets, 0.02 parts by weight of dispersant, 0.02 parts by weight of defoaming agent and 60 parts by weight of solvent were stirred and mixed to obtain a mixed slurry (i.e., coating).
[0093] (2) Composite coating preparation:
[0094] The mixed slurry is coated on the surface of the substrate by electrophoretic deposition technology and cured to obtain an anti-corrosion and wear-resistant integrated composite coating. The conditions of the electrophoretic deposition technology coating process are: the DC voltage is controlled at 90V, the curing temperature is controlled at 120°C, the curing time is 30min, and the thickness of the composite coating is 50μm.
[0095] Example 2
[0096] An anti-corrosion and wear-resistant integrated composite coating and a preparation method and application thereof, comprising the following steps:
[0097] (1) Raw materials for preparing composite coating: by weight: 20 parts by weight of cathode aqueous acrylic emulsion (specifically, aqueous acrylic acid copolymerized with acrylate and methacrylate monomers, purchased from Jiangxi Gaojie Technology Co., Ltd.), 0.5 parts by weight of protonated modified MXene nanosheets, 0.04 parts by weight of dispersant, 0.04 parts by weight of defoaming agent and 90 parts by weight of solvent were stirred and mixed to obtain a mixed slurry (i.e., coating).
[0098] (2) Composite coating preparation:
[0099] The mixed slurry is coated on the surface of the substrate by electrophoretic deposition technology and cured to obtain an anti-corrosion and wear-resistant integrated composite coating. The conditions of the electrophoretic deposition technology coating process are: the DC voltage is controlled at 120V, the curing temperature is controlled at 160°C, the curing time is 60min, and the thickness of the composite coating is 52μm.
[0100] Example 3
[0101] An anti-corrosion and wear-resistant integrated composite coating and a preparation method and application thereof, comprising the following steps:
[0102] (1) Composite coating preparation raw materials: by weight: 16 parts by weight of cathode aqueous acrylic emulsion (specifically, aqueous acrylic acid copolymerized with acrylate and methacrylate monomers, purchased from Jiangxi Gaojie Technology Co., Ltd.), 0.35 parts by weight of protonated modified MXene nanosheets, 0.035 parts by weight of dispersant, 0.035 parts by weight of defoaming agent and 80 parts by weight of solvent were stirred and mixed to obtain a mixed slurry (i.e., coating).
[0103] (2) Composite coating preparation:
[0104] The mixed slurry is coated on the surface of the substrate by electrophoretic deposition technology and cured to obtain an anti-corrosion and wear-resistant integrated composite coating. The conditions of the electrophoretic deposition technology coating process are: the DC voltage is controlled at 105V, the curing temperature is controlled at 145℃, the curing time is 43min, and the thickness of the composite coating is 54μm.
[0105] Comparative Example 1
[0106] 15 parts of water-based acrylic cathode electrophoretic paint (specifically, water-based acrylic acid copolymerized with acrylate and methacrylate monomers, purchased from Jiangxi Gaojie Technology Co., Ltd.), 0.025 parts of dispersant (BYK-166), 0.025 parts of defoamer (BYK-052N) and 80 parts of solvent (deionized water) were prepared into a mixed slurry and mixed at a speed of 400 rpm for 70 minutes. Finally, the water-based acrylic cathode electrophoretic paint anti-corrosion and wear-resistant integrated coating was coated on the surface of Q235 steel by electrophoretic deposition technology, and cured at 140°C for 40 minutes to obtain a water-based acrylic cathode electrophoretic paint coating (WAA), the thickness of which was 53 μm.
[0107] Comparative Example 2
[0108] 15 parts of waterborne acrylic cathode electrophoretic paint, 0.3 parts of MXene nanosheets, 0.025 parts of dispersant (BYK-166), 0.025 parts of defoamer (BYK-052N) and 80 parts of solvent (deionized water) were prepared into a mixed solution and mixed at a speed of 400rpm for 70min; finally, the waterborne acrylic cathode electrophoretic paint anti-corrosion and wear-resistant integrated coating was coated on the surface of Q235 steel by electrophoretic deposition technology. After curing at 140℃ for 40min, a high-performance waterborne acrylic cathode electrophoretic paint anti-corrosion and wear-resistant integrated coating (MXene / WAA) was obtained, and the thickness of the composite coating was 56μm.
[0109] Comparative Example 3
[0110] 15 parts of waterborne acrylic cathodic electrophoretic paint, amino-modified and protonated MXene nanosheets (f + -MXene) nanosheets 0.3 parts, dispersant (BYK-166) 0.025 parts, defoamer (BYK-052N) 0.025 parts and solvent (deionized water) 80 parts were prepared into a mixed slurry, mixed at a speed of 400rpm for 70min, and finally, the water-based acrylic cathode electrophoretic paint anti-corrosion and energy-resistant integrated coating was coated on the surface of Q235 steel by electrophoretic deposition technology. Cured at 140℃ for 40min, a high-performance water-based acrylic cathode electrophoretic paint anti-corrosion and wear-resistant integrated coating (f +-MXene / WAA), the thickness of the composite coating is 54 μm.
[0111] Among them, f + -MX (i.e. f + The preparation method of f-MXene is as follows: 0.2 g of amino-modified MXene is added to 200 mL of 1 mol / L HCl solution, stirred at room temperature at a speed of 250 rpm for 12 hours. After vacuum filtration with a filter membrane, it is washed with deionized water several times and dried in an oven at 60°C for 12 hours to obtain f-MXene. + -MXene.
[0112] Experimental Example 1
[0113] The f was characterized by transmission electron microscopy (TEM, TF20), scanning electron microscopy (SEM, fg-250) and energy dispersive spectroscopy (EDS). + -MXene-P nanosheets were analyzed for their surface morphology and elemental composition. Figure 2 shown. Figure 2 Where (a) is f + -TEM image of MXene-P nanosheets, Figure 2 (b) is f + -SEM image of MXene-P nanosheets, Figure 2 Where (c) is f + - Ti element distribution map of MXene-P nanosheets measured by EDS, Figure 2 (d) is f + -N element distribution map of MXene-P nanosheets measured by EDS, Figure 2 (e) is f + -P element distribution map of MXene-P nanosheets measured by EDS.
[0114] observe Figure 2 (a) and Figure 2 From (b), we can see that f + -MXene-P nanosheets are two-dimensional sheets with a certain degree of transparency. Figure 2 Middle (c), Figure 2 Middle (d) and Figure 2 In (e), it is observed that in f + A large amount of N and P elements were detected in the EDS spectrum of MXene-P nanosheets, which corresponds to BTA-P 4444 The N and P elements in the tetrabutylphosphinothiocyanate ionic liquid in the -Lig composite material also indicate that the modification of MXene nanosheets by 2,5-diaminobenzenesulfonic acid has been achieved.
[0115] Experimental Example 2
[0116] The Zate potential analyzer (DLS) was used to analyze the MX (MXene nanosheets), f-MX, and f + -MX, f-MX-P, f + -MX-P surface potential changes were analyzed and the results were as follows Figure 3 As shown, Figure 3 MX, f-MX, f + -MX, f-MX-P, f + -Potential analysis of the MX-P surface.
[0117] Depend on Figure 3 It can be seen that the Zeta potentials of MX, f-MX, and f-MX-P are -12.3mV, -22.4mV, and -14.3mV, respectively, which indicates that the surfaces of MX, f-MX, and f-MX-P are negatively charged. + -MX, f + The Zate potentials of -MX-P are 5.7mV and 12.1mV respectively, and the surface is positively charged. This is because after protonation, -NH3 + The cationic characteristics of f + -MX, f + -MX-P surface is positively charged. Therefore, it is further proved that the protonation of f-MX and f-MX-P with a hydrochloric acid solution with a concentration of 1 mol / L can make the surface of f-MX and f-MX-P positively charged, which is a good method for preparing parallel arranged f-MX by electrophoretic deposition technology. + -MX / WAA, f + -MX-P / WAA composite coating creates conditions.
[0118] Experimental Example 3
[0119] Electrochemical impedance spectroscopy (EIS) method was used to test the anti-corrosion performance of composite coatings.
[0120] The electrochemical workstation was used to measure the WAA (Comparative Example 1), MX / WAA (Comparative Example 2), f + -MX / WAA (Comparative Example 3), f + -MX-P / WAA (Example 3) was tested for its corrosion resistance by immersing in 3.5wt.% NaCl solution for 1d, 7d, 14d, and 27d. A conventional three-electrode system was used with a surface exposure area of 1cm 2 The aqueous acrylic acid composite coating / Q235 steel sample was used as the working electrode, the calomel electrode (SCE) was used as the reference electrode, and the platinum electrode was used as the counter electrode. The electrochemical impedance spectroscopy (EIS) measurement frequency range was 10 -2 -10 5Hz, AC amplitude is 10mV, and the test is performed after the open circuit potential is stable. ZsimpWin software is used to fit and analyze the EIS data of the composite coating at different immersion times (1d, 7d, 14d, 27d), and the data are shown in Tables 1 and 2.
[0121] Table 1 Electrochemical parameters of the composite coating immersed in 3.5wt.% NaCl solution for 1 day
[0122]
[0123] Table 2 Electrochemical parameters of the composite coating immersed in 3.5wt.% NaCl solution for 27 days
[0124]
[0125] Q c and Q dl They represent coating capacitance and double layer capacitance respectively. c The value is used to evaluate the protective performance of the coating. c The larger the value, the more micropores and defects there are in the coating, and the worse the anti-corrosion performance of the coating. dl Can reflect the corrosion activity of Q235 steel, Q dl The larger the value, the more serious the corrosion of Q235 steel. s , R c and R ct Represent solution resistance, coating resistance and charge transfer resistance respectively. c Indicates the corrosion resistance of the coating, R c The larger the value, the more difficult it is for the corrosive medium to penetrate the coating and reach the metal substrate. + -MX-P / WAA (Example 3) R after immersion in corrosive solution for 27 days c The value is 1.18×10 6 Ω·cm 2 , which is significantly larger than the other coatings. The data in Tables 1 and 2 show that f + -MX-P / WAA has excellent corrosion resistance. When the corrosive medium passes through the composite coating, the corrosion process of the coating / metal system is controlled by the charge transfer resistance R ct Decision, R. ct The larger it is, the better the anti-corrosion performance of the coating.
[0126] By comparing Table 1 and Table 2, it is found that when the WAA coating (Comparative Example 1) is immersed in 3.5wt.% NaCl solution for 27 days, the R ct The value is from 5.64×10 6 Ω·cm 2 Down to 6.09×10 4 Ω·cm2 .Q c , Q dl The values range from 2.40×10 -10 Ω·cm -2 ·S n Down to 1.47×10 -9 Ω·cm -2 ·S n , 2.80×10 -7 Ω·cm -2 ·S n Down to 5.68×10 -5 Ω·cm -2 ·S n This indicates that corrosive substances can penetrate the WAA coating to reach the Q235 steel substrate, causing serious corrosion to the Q235 steel. ct The value ranges from 1.41×10 7 Ω·cm 2 Reduced to 6.74×10 5 Ω·cm 2 MX / WAA's anti-corrosion performance is improved compared to WAA. This is because the WAA coating produces a large number of micropores and defects due to the evaporation of water during the curing process, providing diffusion channels for the invasion of corrosive media. The few layers of MX have a large specific surface area. Adding it to water-based acrylic as a coating filler enhances the density of the coating and forms a "maze effect" in the water-based acrylic coating, extending the diffusion path of the corrosive medium.
[0127] When f + -MX / WAA (Comparative Example 3) was immersed in 3.5wt.%NaCl solution for 27 days. ct The value ranges from 3.06×10 8 Ω·cm 2 Reduced to 1.31×10 7 Ω·cm 2 .Q c , Q dl The values are 2.28×10 -10 Ω·cm -2 ·S n , 6.66×10 -7 Ω·cm -2 ·S n , are greater than MX / WAA. This indicates that f + -MX / WAA has fewer micropores and defects than MX / WAA, and it is difficult for the corrosive medium to penetrate the micropores of the coating to reach the metal substrate. +-MX / WAA has better anti-corrosion performance than MX / WAA. The above results show that the amino modification of MX with 2,5-diaminobenzenesulfonic acid and f + -MX is distributed in parallel in the coating by electrophoretic deposition technology, which overcomes the shortcomings of random distribution and easy agglomeration of MX nanosheets in the coating. + -MX forms a continuous interface and a "zigzag effect" in the water-based acrylic coating. The MX arranged in parallel in the coating has a more excellent barrier performance. This is because the MX arranged in parallel in the coating can greatly exert its advantages of high specific surface area and effectively prevent corrosive substances from penetrating into the metal substrate. Therefore, f + -MX / WAA exhibits superior corrosion protection compared to MX / WAA.
[0128] f + -MX-P / WAA (Example 3) was immersed in 3.5wt.% NaCl solution for 27 days, R ct The value ranges from 1.97×10 9 Ω·cm 2 Reduced to 4.01×10 7 Ω·cm 2 .f + -Q in MX-P / WAA c , Q dl The values are 1.79×10 -10 Ω·cm -2 ·S n , 2.83×10 -10 Ω·cm -2 ·S n , are greater than f + -MX / WAA, which indicates that f + -Micropores and defects in MX-P / WAA and f + -MX / WAA is further reduced, and corrosive media are difficult to pass through f + -The micropores in MX-P / WAA penetrate to the coating / metal interface. Therefore, f + -MX-P / WAA's anti-corrosion performance is significantly better than f + -MX / WAA. By comparing the above experimental results, we can see that on the one hand, the electrophoretic deposition technology is used to + -MX-P is added to the cathode water-based acrylic resin as a coating filler, + -MX-P is arranged in a directional manner in the coating to form a continuous interface and a zigzag diffusion path, which overcomes the disadvantage of MX being easily agglomerated in the coating, enhances the density of the coating, and prolongs the diffusion path of the corrosive medium. + -BTA-P on MX nanosheets4444 -Lig forms an adsorption film on the surface of Q235 steel substrate to block the invasion of corrosive media, and BTA-P 4444 The lignin in the -Lig composite contains phenolic hydroxyl groups, which effectively capture oxygen free radicals to form resonance-stabilized semiquinone free radicals, blocking the chain reaction and thus further delaying the corrosion of Q235 steel.
[0129] Experimental Example 4
[0130] Composite coating wear resistance test
[0131] Using a CSM friction and wear tester (Antonpa, CSM, TRB3, Switzerland), under the experimental conditions of load 2N, frequency 2Hz, friction range 5mm, and friction time 10min, comparative example 1 (WAA), comparative example 2 (MX / WAA), comparative example 3 (f + -MX / WAA), Example 3 (f + -MX-P / WAA) provides the coefficient of friction of the composite coating (such as Figure 4 The wear volume of the composite coating was measured using a confocal microscope (DCM8). Figure 4 (b)), and finally the wear morphology of the composite coating was observed by field emission scanning electron microscopy, and the results were as follows Figure 5 shown. Figure 5 (a) is the SEM morphology of the wear track of WAA. Figure 5 (b) is the SEM morphology of the wear track of MX / WAA. Figure 5 Where (c) is f + -SEM morphology of the wear track of MX / WAA, Figure 5 (d) is f + -SEM morphology of the wear track of MX-P / WAA.
[0132] observe Figure 4 As shown in (a), the friction coefficient of WAA starts to rise slowly in the initial stage of friction, and rises sharply to 0.843 when the friction time increases to 100s. The friction coefficient of MX / WAA after stabilization (0.704) is lower than that of WAA. This is due to the self-lubricating properties of MX, which forms a lubricating layer during the friction process. + -The friction coefficient of MX / WAA rises slowly in the initial stage of friction, and is significantly lower than that of MX / WAA. This is because the hydrophilicity of MX modified by 2,5-diaminobenzenesulfonic acid is enhanced, which improves the dispersibility of MX in water-based acrylic coatings. + -The parallel distribution of MX in the waterborne acrylic coating makes the composite coating surface smoother and flatter. +The friction coefficient of -MX / WAA is low at the initial stage of friction, and rises sharply to 0.655 when the friction time is greater than 500s. This is because the wear of the coating increases the roughness of the coating surface and increases the friction force. + - The friction coefficient of MX-P / WAA tends to be flat during the entire friction process and the friction coefficient is reduced to 0.103. This is because the lubricating properties of MX and BTA-P 4444 -Lig's synergistic effect makes f + -MX-P / WAA wear resistance ratio f + -MX / WAA is superior. In addition, the wear volume (such as Figure 4 The variation trend of (b) is similar to that of the friction coefficient. The wear volume of the WAA coating is 6.44×10 6 μm -3 Compared with pure WAA coating, MX / WAA, f + -MX / WAA, f + -The wear volume of MX-P / WAA composite coating was reduced to 2.54×10 5 μm -3 , 1.25×10 5 μm -3 and 7.77×10 4 μm -3 In summary, + -MX-P / WAA has excellent wear resistance.
[0133] like Figure 5 As shown in (a), the wear mark of WAA is wider and a large number of wear cracks can be observed. At the same time, a small amount of debris is distributed around the wear mark of WAA. The reason for the above phenomenon is that the water-based acrylic coating falls off during the friction process, resulting in the wear of Q235 steel.
[0134] The wear track of MX / WAA is as follows Figure 5 As shown in (b), the wear trace is narrower than that of WAA, proving that MX as a coating filler can improve the wear resistance of the coating. + -Only a small amount of wear cracks and shallow wear marks were observed on the surface of the MX / WAA coating (e.g. Figure 5 This is due to the parallel distribution of f in the coating. + -MX orientation has a certain inclination angle with the crack propagation direction, which will hinder the crack propagation and reduce the coating peeling phenomenon. + -Wear marks on MX-P / WAA Figure 5 As shown in (d), f + -MX-P / WAA has the shallowest wear depth and no obvious wear cracks are observed. This is because the electrophoretic deposition technology makes the f+ -MXene-P is distributed in parallel in the coating, further reducing the agglomeration of MX in the coating, reducing the concentration of shear stress during friction, and reducing the peeling of the coating. + - The parallel distribution of MXene-P in the coating can quickly form a friction protection film covering the largest sliding surface area during the friction process, giving full play to the f + -MXene-P has self-lubricating properties. And BTA-P loaded on MXene-P 4444 The polar elements N and P in -Lig react with the metal substrate to form a tribochemical reaction film during the friction process, thereby further enhancing the f + -MX-P / WAA composite coating wear resistance. + -MX-P / WAA composite coating has excellent wear resistance.
[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An anti-corrosion and wear-resistant integrated composite coating, characterized in that: The coating comprises a composite coating in which protonated modified MXene nanosheets are distributed in parallel in a cathode acrylic coating.
2. A method for preparing an anti-corrosion and wear-resistant integrated composite coating, characterized in that: For preparing the anti-corrosion and wear-resistant integrated composite coating according to claim 1, the preparation method comprises the following steps: 10-20 parts by weight of cathode aqueous acrylic emulsion, 0.1-0.5 parts by weight of protonated modified MXene nanosheets, 0.02-0.04 parts by weight of dispersant, 0.02-0.04 parts by weight of defoamer and 60-90 parts by weight of solvent are stirred and mixed to obtain a mixed slurry; The mixed slurry is moved toward the cathode under the action of the electric field force by the electrophoretic deposition technology and coated on the surface of the substrate, and solidified to obtain the anti-corrosion and wear-resistant integrated composite coating.
3. The method for preparing the anticorrosion and wear-resistant integrated composite coating according to claim 2, characterized in that: The conditions in the electrophoretic deposition coating process are: the DC voltage is controlled at 90-120V, the curing temperature is controlled at 120-160°C, and the curing time is 30-60min.
4. The method for preparing the anticorrosion and wear-resistant integrated composite coating according to claim 2, characterized in that: The method for preparing the protonated MXene nanosheets comprises the following steps: Aminated modified MXene: MXene nanosheets, 2,5-diaminobenzenesulfonic acid and water are first mixed and reacted to obtain amino-modified MXene nanosheets; the mass ratio of the MXene nanosheets, the 2,5-diaminobenzenesulfonic acid and the water is (1-2): (1-2): 1; Composite material grafted with MXene: the amino-modified MXene nanosheets, water and tetrabutyl phosphohydroxide benzotriazole lignin composite material are mixed for a second time, and grafted to obtain MXene nanosheets grafted with tetrabutyl phosphohydroxide benzotriazole lignin composite material; Protonated MXene: The MXene nanosheets grafted with tetrabutylphosphohydroxide benzotriazole lignin composite material are thirdly mixed with 1 mol / L HCl solution and protonated to obtain the protonated modified MXene nanosheets.
5. The method for preparing the anticorrosion and wear-resistant integrated composite coating according to claim 4, characterized in that: Before the amination modification of MXene, the MXene is also pretreated; The pretreatment process includes: After MXene and dimethyl sulfoxide are mixed, a first centrifugation is performed, and the nanosheets obtained by the first centrifugation are mixed with water, and ultrasonication and a second centrifugation are performed in sequence to obtain pretreated MXene nanosheets.
6. The method for preparing the anticorrosion and wear-resistant integrated composite coating according to claim 4, characterized in that: The mass ratio of the amino-modified MXene nanosheets, the water and the tetrabutylphosphohydroxide benzotriazole lignin composite material is (1-2): (1-2): (2-3).
7. The method for preparing the anticorrosion and wear-resistant integrated composite coating according to claim 4, characterized in that: The mass ratio of the MXene nanosheet grafted with tetrabutylphosphohydroxide benzotriazole lignin composite material and the 1 mol / L HCl solution is (1-2): (100-300).
8. An anti-corrosion and wear-resistant integrated coating, characterized in that: The coating is used to prepare the anti-corrosion and wear-resistant integrated composite coating according to claim 1, or is used in the preparation method of the anti-corrosion and wear-resistant integrated composite coating according to any one of claims 2 to 7. The coating comprises the following preparation raw materials in parts by weight: 10-20 parts by weight of cathode aqueous acrylic emulsion, 0.1-0.5 parts by weight of protonated modified MXene nanosheets, 60-90 parts by weight of solvent, 0.02-0.04 parts by weight of dispersant, and 0.02-0.04 parts by weight of defoamer; The protonated modified MXene nanosheet is a MXene nanosheet grafted with tetrabutyl phosphohydroxide benzotriazole lignin composite material and protonated with 1 mol / L HCl.
9. The anti-corrosion and wear-resistant integrated coating according to claim 8, characterized in that: The dispersant includes one or more of BYK-104s, BYK-166 and K270; The defoamer includes one or more of BYK-035, BYK-052N and BYK-077; and the solvent is water.
10. An application of an anti-corrosion and wear-resistant integrated composite coating, characterized in that: The anti-corrosion and wear-resistant integrated composite coating is the anti-corrosion and wear-resistant integrated composite coating described in claim 1 above, or the anti-corrosion and wear-resistant integrated composite coating obtained by the preparation method described in any one of claims 2-7, and the anti-corrosion and wear-resistant integrated composite coating is applied in the field of marine corrosion protection.
Citation Information
Patent Citations
MXene / polyaniline nano-composite anticorrosive and antibacterial coating and preparation method thereof
CN113122106A
MXene and carbon nano tube synergistically modified polyurethane anticorrosive paint as well as preparation method and construction process thereof
CN114276743A
High-density multi-scale waterborne epoxy anti-corrosion coating as well as preparation method and application thereof
CN116200091A
Anticorrosive and wear-resistant MXene composite coating with bionic structure as well as preparation and application of anticorrosive and wear-resistant MXene composite coating
CN117888162A
Anti-corrosion and wear-resistant integrated coating as well as preparation method and application thereof
CN117986972A
